Contemporary Foreign Economic Relations of Russia with the Countries of Northern Europe - A. M. Volkov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2021)
Recently new problems have arisen that have complicated Russia’s foreign economic relations with foreign countries. The countries of Northern Europe were no exception. The economic situation in many countries was far from optimal. Problems with economy took place in the euro area. A significant drop in oil prices led to a slowdown in economic growth in the Russian Federation and a sharp decline of ruble exchange rate. Since 2014, various Western sanctions have emerged, followed by retaliatory sanctions from Russia. Against this background, the analysis of the dynamics of Russian economic relations with the Nordic countries is of particular interest. A sharp decline in foreign economic indicators occurred in 2015–2016. Subsequent development has shown different dynamics. On the one hand, by the end of the 2010s foreign trade with Finland and Sweden did not reach the level of 2013–2014 (primarily due to the decline in oil prices), but on the other, foreign trade indicators with Denmark and Norway were exceeded (due to Russian exports). Year 2020 brought new problems – the coronavirus pandemic and the associated restrictions on the movement of goods, services and people, as well as the rupture of production chains, which had an impact on foreign economic relations – and exacerbated the old ones: a new sharp drop in oil prices and a new depreciation of ruble. The article reveals the features of the general dynamics and commodity structure of foreign trade with each of the observed countries. The significant dependence of Russian exports, primarily on energy supplies, is considered in detail. Special attention is given to the general dynamics of foreign direct investment in Russia. The problems of modern development of Russian export and import were analyzed.